Investigation of the scintillation properties of plastic scintillator based on 2,5-diaryloxadiazole alkyl derivative - Zhmurin, P.N.; Yelisieiev, D.A.; Yelisieieva, O.V.; Pereymak, V.N.; Gurkalenko, Yu.A. (Functional Materials, 2019)
An activator is synthesized that could be dissolved up to 40 % in a polystyrene matrix without precipitation of a single phase. Detailed studies of the spectral and scintillation properties of plastic scintillators activated by the new activator have been carried out. It is shown that while the concentration of the activator increases, the proportion of molecules bound to the associates increases as well. When the activator concentration is higher than 10 %, a slow component appears in the scintillation pulse as a result of triplet-triplet annihilation. According to the shape of the scintillation pulse, it is established that the lifetime of the triplet excited states in the new activator is about 10 ns, what is not sufficient for obtaining a plastic scintillator with the effective neutron-gamma discrimination properties.